Umer Chapra's Critique of The Western Concept of Welfare State - Khoirul Umam; Achmad Jalaludin (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2023)
This study aims to dissect Chapra's critique of the Western concept of welfare state, and his thoughts on welfare state in Islam in order to solve the problem of impasse in the thinking of modern economists. This research provides enlightenment on how the concept of the welfare state is actually in Islam through the idea of Umer Chapra. The relevance of his thoughts is juxtaposed with the current state of the Indonesian state. This research is expected to be a strong reference for academics and practitioners in addressing the concept of the welfare state. The method in this study uses a qualitative approach with a library research model. Data is obtained from various sources, such as Umer Chapra's master book in the discussion of welfare states, journals, or news info from newspapers. The results of the study show that Umer Chapra's criticism is very comprehensive. Chapra focused in his mind on the Islamic worldview, economic strategy, and welfare state goals. Islamic values are instilled in the strategy of regulating the country's economy. As for its relevance to the state of Indonesia, the results of the analysis show that Chapra's criticism of the welfare state and his thoughts are still relevant to the current state of Indonesia.